POSHAN’s abstract digest on maternal and child nutrition research - Issue 47 - Avula, Rasmi (International Food Policy Research Institute, 2022)
Season’s greetings! The 47th issue of POSHAN’s Abstract Digest features studies on maternal nutrition, anemia, and infant and young child feeding (IYCF) practices. The maternal nutrition articles include a modeling study that examines the importance of prenatal nutrition for reducing the global burden of non-communicable diseases, and a gap analysis study to identify key elements to strengthen maternal nutrition counselling during routine health services. There are two anemia articles: one examines the association of adolescent anemia and physical growth with learning outcomes, while the other investigates the prevalence and determinants of anemia among men. Among the two articles covering IYCF practices, one assesses food group consumption patterns among children in 59 countries and the other investigates the association between IYCF practices and nutrition indicators. Other interesting studies in this issue include two articles based on learnings from interventions through women’s self-help groups, an assessment of anthropometric data quality in India’s National Family Health Survey, another on implementation characteristics of father-inclusive interventions in low- and middle-income countries, and one on the perceptions, risk factors, and behaviors of overweight adults.